Literatur Review Idarucizumab Pharmacology as Dabigatran Antidotes : Mechanism of action, pharmacokinetics, efficacy and safety - Tanti, Yunita Dwi (Brawijaya University, 2019)
A B S T R A C TBackground: Atrial Fibrillation (AF) is a common abnormal heart rhythm , responsible for high rate of cardiovascular and cerebrovascular morbidity and mortality. The prevalence of AF in the general population is about 3%. Stroke patients with AF have a high mortality rate up to 50% in one year, compared to stroke patients without AF which is 27%. Dabigatran etexilate is an oral thrombin inhibitor that had been approved for stroke prevention in nonvalvular atrial fibrillation patients and also has a role in venous thromboembolism (VTE) prevention and treatment. Since dabigatran usage result in hemorrhage and might lead to immediate intervention or surgery, a specific reversal agent (antidote) is highly needed during this emergency situation. A specific reversal agent for dabigatran is Idarucizumab.Discussion:Idarucizumab has a high affinity to both free and thrombin-bound dabigatran, and also its metabolite, acylglucoronide. Idarucizumab can neutralize the anticoagulant effect from dabigatran by binding them to form a stoichiometric complex with 1:1 molar ratio. Idarucizumab and dabigatran interaction have a very fast on-rate and a slow off-rate resulting in a stable Idarucizumab-dabigatran complex which elicits its effect in a few minutes.Conclusion: Idarucizumab can reverse the effects of dabigatran anticoagulants in a few minutes by forming a stable complex. Some study concerning Idarucizumab efficacy and safety on healthy patients and patients with renal disorder, showed that Idarucizumab can be well tolerated. There was no severe adverse event, dose-dependent event, drop-out due to an adverse event, and no relevant clinical findings were reported for vital sign, physical examination, electrocardiogram, cardiac telemetry, or laboratory parameters.Keywords:Idarucizumab, Dabigatran, stroke, Nonvalvular Atrial Fibrillation